Differences in AM fungal root colonization between populations of perennial Aster species have genetic reasons - Pánková, Hana; Münzbergová, Zuzana; Rydlová, Jana; Vosátka, Miroslav (Oecologia, 2008)
We tested the hypothesis whether differences between plant populations in root colonization by arbuscular mycorrhizal (AM) fungi could be caused by genetic differentiation between populations. In addition, we investigated whether the response to AM fungi differs between plants from different populations and if it is affected by the soil in which the plants are cultivated. We used Aster amellus, which occurs in fragmented dry grasslands, as a model species and we studied six different populations from two regions, which varied in soil nutrient concentration. We found significant differences in the degree of mycorrhizal colonization of plant roots between regions in the field. To test if these differences were due to phenotypic plasticity or had a genetic basis, we performed a greenhouse experiment. The results suggested that Aster amellus is an obligate mycotrophic plant species with a high dependency upon mycorrhiza. Plant biomass was affected only by soil, and not by population or the interaction between the population and the soil. Mycorrhizal colonization was significantly affected by all three factors (soil, population, interaction of soil and population). Plants from the population originating from the soil with lower nutrient availability developed more mycorrhiza even when grown in soil with higher nutrient availability. The correspondence between mycorrhizal colonization of plants in the field and in both soils in the pot experiment suggests that the observed differences in root colonization have a genetic basis.
Keywords: půdní mikrobiologie; populační dynamika; mykorhiza; Population Dynamics; Mycorrhizae; Seasons; Soil; půda; Soil Microbiology; Biomass; Plant Roots; kořeny rostlin; biomasa; Aster; roční období; Aster Plant